STUDI TINGKAT KEBERHASILAN DAN SOLUSI REHABILITASI MANGROVE PADA TELUK AMBON BAGIAN DALAM, PROVINSI MALUKU - Irwanto Irwanto; Andjela Sahupala; Fanny Soselisa (MARSEGU : Jurnal Sains dan Teknologi, 2024)
This study evaluates the success and failure of mangrove rehabilitation in Inner Ambon Bay, focusing on environmental factors, planting techniques, and habitat conditions. The research was conducted over 12 months, from May 2022 to April 2023, using descriptive quantitative and qualitative methods. Primary data were collected through field observations and interviews, while secondary data from relevant institutions were analyzed using Survival Rate and Growth Rate formulas. Out of 1,260 planted mangrove seedlings, only 29 survived, yielding a success rate of 2.3%. Failure factors include inadequate substrate, narrow intertidal zones due to reclamation, and wave disturbances. Proposed solutions include substrate modification, species zoning adjustments, and mechanical protection for seedlings. These findings highlight the importance of ecologically integrated approaches in mangrove rehabilitation programs to ensure long-term success.